Co-localization of Interleukin-1α and Annexin A2 at the plasma membrane in response to oxidative stress - Novák, Josef; Vopálenský, Václav; Pospíšek, Martin; Vedeler, Anni (Cytokine (Philadelphia, Pa. Print), 2020)
Interleukin-1α (IL-1α) and Annexin A2 (AnxA2) are pleiotropic molecules with both intracellular and extracellular roles. They share several characteristics including unconventional secretion aided by S100 proteins, anchoring of the externalized proteins at the outer surface of the plasma membrane and response to oxidative stress. Although IL-1α and AnxA2 have been implicated in a variety of biological processes, including cancer, little is known about the mechanisms of their cellular release. In the present study, employing the non-cancerous breast epithelial MCF10A cells, we demonstrate that IL-1α and AnxA2 establish a close association in response to oxidative stress. Stress conditions lead to translocation of both proteins towards lamellipodia rich in vimentin and association of full-length IL-1α and Tyr23 phosphorylated AnxA2 with the plasma membrane at peripheral sites depleted of F-actin. Notably, membrane-associated IL-1α and AnxA2 preferentially localize to the outer edges of the MCF10A cell islands, suggesting that the two proteins participate in the communication of these epithelial cells with their neighboring cells. Similarly, in U2OS osteosarcoma cell line both endogenous IL-1α and transiently produced IL-1α/EGFP associate with the plasma membrane. While benign MFC10A cells present membrane-associated IL-1α and AnxA2 at the edges of their cell islands, the aggressive cancerous U2OS cells communicate in such manner also with distant cells.
Keywords: Female; oxidační stres; Cell Line, Tumor; Interleukin-1alpha; ženské pohlaví; Oxidative Stress; S100 Proteins; lidé; Epithelial Cells; Annexin A2; Phosphorylation; fosforylace; aktiny; interleukin-1alfa; Actins; proteiny S100; buněčná membrána; annexin A2; epitelové buňky; nádorové buněčné linie; Cell Membrane; Humans